Taṣmīm Mudawwanah Al-Munāẓarah Al-Arabiyyah ‘ala Asās Al-Sam’iyyah Al-Baṣariyyah. - Muhammad Ahsan Thoriq; Mohammad Ahsanuddin; Yoke Suryadarma (Arabic Education Program IAIN Pekalongan, 2022)
This study aims to describe the prototype designs of the Corpus of Arabic debates. The method used is Research and Development (R&D) which purpose to produce product prototype designs. The author performs three stages of several stages of the existing method. First the analysis, second the planning, and third the development. The research data is in the form of audio-visual debates from the 'Qatardebate' account and debate technical handbooks. All data were collected in a corpus of website-based debates. The results showed that (a) the design of the debate corpus was carried out in two stages, namely the collection of needs and the design of the debate corpus, (b) to create an appropriate debate delivery structure, it must synthesize debate practices and guidelines applied, and (c) the Arabic debate corpus serves to analyze the use of corcondance and the frequency of words used by debaters.